Efficacy of Patrapinda Swed in the Management of Sandhigat Vata w.s.r. to Osteoarthritis (AYUSHDHARA, 2023)
Sandhigata Vata is a Vata vitiated disease, characterized by Sandhishoola, Shopha, Sandhigrah, Sandhisphutan & Sparsha asahayta. In Ayurveda we can correlate Sandhigat vata with Osteoarthritis. Its common symptoms are pain & stiffness. As disease progresses it may cause morbidity and work disability. The single most cause of locomotor disability & major challenge to health care. Joint pain is the global problem for patients with almost 70 to 80% of the world population are suffering from it. In Ayurvedic classics, Acharyas have mentioned various Shaman procedures like Snehan, Swedan to provide better relief from the pain & swelling to restore the mobility. Patrapinda sweda is a type of Swedna. It is commonly performed for the Sandhigat vata. The present study is done to evaluate the efficacy of Patrapind sweda in the management of Sandhigata vata w.s.r to osteoarthritis. The study was conducted at Panchakarma Department of Shree Saptashrugi Ayurved Mahavidyala and Hospital, Panchvati, Nashik, Maharashtra.Total number of 10 patients between age 40-70 years having symptoms of Sandhigat vata were selected. It is observed that Patrapinda sweda done as per the textual methods is highly effective in Sandhigata vata.